2017
DOI: 10.1016/j.marpol.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Can the United States have its fish and eat it too?

Abstract: As domestic affluence increases, nations advocate for conservation policies to protect domestic biodiversity that often curtail natural resource production activities such as fishing. If concomitant consumption patterns remain unchanged, environmentally-conscious nations with high consumption rates such as the U.S. may only be distancing themselves from the negative environmental impacts associated with consuming resources and commodities produced elsewhere. This unintended displacement of ecosystem impacts, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Given the complex connectivity of global markets and ecological systems, it is challenging to directly measure these transferred or displaced impacts. However, recent research has identified displaced environmental impact across a range of natural resource policies, including those governing fisheries management (Chan & Pan, 2016;Helvey, Pomeroy, Pradhan, Squires, & Stohs, 2017;Rausser, Hamilton, Kovach, & Stifter, 2009), biodiversity protection (Lenzen et al, 2012;Weinzettel, Hertwich, Peters, Steen-Olsen, & Galli, 2013), forest preservation (Gan & McCarl, 2007;Mayer, Kauppi, Angelstam, Zhang, & Tikka, 2005;Meyfroidt & Lambin, 2009), and land use (Kastner, Kastner, & Nonhebel, 2011;Meyfroidt, 2017). Despite growing evidence (Box 1), there has been relatively little effort within and across resource sectors to adequately integrate this work into policy discussions in a manner that transcends disciplinary, sectoral, or other boundaries.…”
Section: Recognizing How Environmental Impacts Can Be Displacedmentioning
confidence: 99%
“…Given the complex connectivity of global markets and ecological systems, it is challenging to directly measure these transferred or displaced impacts. However, recent research has identified displaced environmental impact across a range of natural resource policies, including those governing fisheries management (Chan & Pan, 2016;Helvey, Pomeroy, Pradhan, Squires, & Stohs, 2017;Rausser, Hamilton, Kovach, & Stifter, 2009), biodiversity protection (Lenzen et al, 2012;Weinzettel, Hertwich, Peters, Steen-Olsen, & Galli, 2013), forest preservation (Gan & McCarl, 2007;Mayer, Kauppi, Angelstam, Zhang, & Tikka, 2005;Meyfroidt & Lambin, 2009), and land use (Kastner, Kastner, & Nonhebel, 2011;Meyfroidt, 2017). Despite growing evidence (Box 1), there has been relatively little effort within and across resource sectors to adequately integrate this work into policy discussions in a manner that transcends disciplinary, sectoral, or other boundaries.…”
Section: Recognizing How Environmental Impacts Can Be Displacedmentioning
confidence: 99%
“…Our analysis includes all Alaska fisheries and is arguably one of the larger analyses of fishing policy outcomes to date. Although not investigated here, there is also evidence that spillover may occur between fishing regions or countries and therefore an even broader scope may be appropriate ( 21 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also considered to have contributed to a reduction in effort and landings of swordfish on the U.S. West Coast. Continued assessment of the economic impacts of these (and potential) regulations and closures is important to ensure thorough evaluation of the trade-off between bycatch reduction and economic opportunity; especially in the context of absolute bycatch impact (which for the DGN is comparatively low; Savoca et al, 2020), and considering the potential for "leakage" and "spillover" of the bycatch problem for many HMS (Chan and Pan, 2016;Helvey et al, 2017).…”
Section: The Drift Gillnet Fisherymentioning
confidence: 99%